Ájtte Collection - Göran Sjöberg (Swedish Mountain and Sami Museum, 2013)
Ájtte Museum is one of the museums in Sweden that actively works with the collection and preservation of natural history material. The purpose of the collection is to build a special collection with the overall heading: "nature of the mountains". The collected material includes birds, mammals, fish, fungi, minerals, rocks and botanicals. The material constituting the Natural history collections are donated by private persons, the police (“state wildlife”) and other museums and institutions. In addition, the museum also conducts its own active collection activities.

Currently, the museum holds over 19,000 natural history objects in its database /collection. The collections are searchable in the museum common database: http://collections.ajtte.com/ and thus accessible to researchers, students and other interested but also useful for educational purposes.

The collections are stored in climate-controlled archives so that they can be preserved in a safe and secure way for the future. Our goal is that these unique collections will come to attention of the special interest researcher and be a resource to taxonomic and morphological studies on the species of Northern Sweden.

The insect collections are the largest part of the natural history collections of Ájtte museum, with more than 14,500 specimens, mainly including beetles and butterflies with a northern provenance. The beetles (Coleoptera) of this collection were donated by Sven-Erik Nilsson’s estate (2003). The butterflies (Lepidoptera) are from the Jokkmokk area and consists of approximately 1 200 specimens belonging to 400 different species, and was donated by Roger Engelmark (Professor Emeritus, University of Umeå).

The museum's collection of reindeers (Rangifer tarandus) is very extensive, perhaps the world's largest. The collection consists of osteological material with over 1 000 skulls, with antlers and jaws from both adult and young animals of both sexes. This well-documented material of reindeer has been collected from the whole Swedish range of distribution. The collection was previous held by the Swedish Museum of Natural History, but in 2010 it was taken over by Ájtte museum. The material was collected by the researcher Folke Skuncke during the middle of the 19th century.
Keywords: Occurrence; Specimen; Occurrence; OCCURRENCE; Biological Sciences; Biologi